The use of MM/QM calculations of 13 C and 15 N chemical shifts in the conformational analysis of alkyl substituted anilines - Abraham, Raymond J (Magnetic resonance in chemistry : MRC, 2020)
© 2019 John Wiley & Sons, Ltd.